Multisensory Integration Is Modulated by Hypnotizability. Issue 2 (3rd April 2021) - Mioli, Alessandro; Diolaiuti, Francesca; Zangrandi, Andrea; Orsini, Paolo; Sebastiani, Laura; Santarcangelo, Enrica L.
ABSTRACT: This study investigated multisensory integration in 29 medium-to-high (mid-highs) and 24 low-to-medium (mid-lows) hypnotizable individuals, classified according to the Stanford Hypnotic Susceptibility Scale, Form A. Participants completed a simultaneity judgment (SJ) task, where an auditory and a visual stimulus were presented in close proximity to their body in a range of 11 stimulus onset asynchronies. Results show that mid-highs were prone to judge audiovisual stimuli as simultaneous over a wider range of time intervals between sensory stimuli, as expressed by a broader temporal binding window, when the visual stimulus precedes the auditory one. No significant difference was observed for response times. Findings indicate a role of hypnotizability in multisensory integration likely due to the highs' cerebellar peculiarities and/or sensory modality preference.